Interest of right? : the process and politics of a diplomatic conference on copyright - Ayyar, R. V. Vaidyanatha (1998)
Highlights the forces and ideas that influenced the outcome of the World Inellectual Property (WIPO) Diplomatic Conference. discusses the critial roles of the different interest groups in the articulation of various economic and other issues that held the centre-stage in the negotiations.